STUDIES ON ECONOMIC TRAITS IN SUCCESSIVE GENERATIONS OF SELFING IN SUGARCANE (SACCHARUM SPP.) - Anna Durai, A; Hemaprabha, G; Rafee Viola, V; Sarath Padmanaban, T.S.; Lakshmi, K (Journal of Sugarcane Research, 2020)
Selfing is one of the classical methods with demonstrated merits to understand parental worthiness, achieving homozygosity and for removing the deleterious genes from the genome. The selfed progenies of S1, S2 and S3 generation of sugarcane clones viz., Co 775, Co 99008, Co 0304, Co 2000-10, Co 0112 and MS 68/47 and S6 and S7 progenies of Co 1148 were studied for homozygosity in successive generations of selfing, level of inbreeding depression and transgressive segregation for important economic traits. A narrow level of variation for HR Brix and wide variation for number of millable canes and moderate level of variation for cane thickness was observed in S1, S2 and S3 generations. The genotypes with least variation among the selfed progenies in preceding generation of selfing did not show the same response in succeeding generations of selfing indicating that the genotypes behave differently in successive generations of selfing during the process of attaining homozygosity. The inbreeding individuals of 1148-13-11-2-237 and 1148-S4-247 depicted the least variation for the traits studied in later generations of selfing. Some of the inbreeding individuals from early generation of selfing of Co 775, MS 68/47, and Co 0112 for number of millable canes, Co 99008, MS 68/47 and Co 0112 for HR Brix and MS 68/47, Co 0112 for cane thickness surpassed their respective parents in their performance. HR Brix was the only trait which was least affected by inbreeding depression and greater level of inbreeding depression was observed for cane thickness. Though inbreeding was observed in early generation of selfing for number of millable canes, no inbreeding depression was observed for the trait in succeeding generations of selfing. Inbreds with higher level of homozygosity in the later generation of selfings viz., S6-2-59 and S6-2-60, S6-2-63 and S6-2-73 and S6-2-66 and S6-2-69 of Co 1148 developed in this study may be utilized for hybrid seed production in sugarcane.